The lighthouse [videorecording (Blu-Ray)] - Eggers, Robert, 1983-; Eggers, Max; Dafoe, Willem; Pattinson, Robert, 1986-; Karaman, Valeriia, 1994-; Korven, Mark; Blaschke, Jarin, 1978- (Lionsgate, 2020)
A hypnotic and hallucinatory tale of two lighthouse keepers on a remote and mysterious New England island in the 1890s. As an approaching storm threatens to sweep them from the rock and strange apparitions emerge from the fog, each man begins to suspect that the other has become dangerously unmoored.